El Derecho a la Salud Intercultural: Caso Comunidades Indígenas de la Parroquia La Esperanza Provincia de Imbabura – cantón Ibarra - Calderón Morales, Camila Patricia (2024)
This Report of the Final Degree Project “The Right to Intercultural Health: Case of Indigenous Communities of the La Esperanza Parish, Province of Imbabura – Ibarra Canton”, the main point to start this investigation will be to determine compliance with current legal regulations and the application of conventional and ancestral medical practices that guarantee the intercultural health of the communities of La Esperanza Parish. The mixed approach (qualitative and quantitative) was applied through interviews using cards with authorities of the sector, the area and users of the Parish who attend the health center by means of a questionnaire, this, with the purpose to check whether or not current regulations are complied with\; It was developed through the socio-legal method, since the documentary review was applied, which was main to meet the objectives of this work, as well as with criteria from authors who knew how to express how intercultural health is treated and from what perspectives they see it. . The research responds to line 12: inequities, exclusions, inequalities and human rights. Through this line, the research seeks to find a sense of justice within society, ensuring that the knowledge obtained from the study can promote social awareness\; taking into account that behind the study of hate speech, there is hidden the interest of safeguarding equality between individuals, not only at a legal level, but also at a social level, recognizing that Law is a science that, due to its nature, can achieve this target and intervene in a timely manner to combat inequality.